The Interactive Factors Contributing to Fear of Death - Rezapour, Mahdi (Frontiers in Psychology, 2022)
Despite the importance of the object of death, there is a limited comprehensive statistical technique that could highlight the real association between fear of death and other variables. Thus, this study is conducted to first reduce dimensionality of dataset by only considering important variables by means of the recursive feature elimination, followed by removal of the multicollinear variables. Finally, we account for multidimensionality of the dataset by considering all pairwise interaction terms across considered variables. The results highlighted, for instance, although being married, older and female offset the negative effects of fear of death, their impacts are multiplicative. Also, those who think cryonic is desirable are associated with higher death fear. However, contrary to the majority of past studies, the associations of almost all predictors are multidimensional. For instance, while belief in cryonics is positively associated with fear of death, its association varies based on the trouble individuals are experiencing that someday they would not be alive, and their marital status.